SOCIAL DELEGITIMATION OF RELIGIOUS OBLIGATION: Zakat, Infaq, and Shodaqoh Traditions among Transnational Madurese Migrant Workers of Indonesia-Malaysia - Hariyanto, Erie; Wardi, Moch Cholid; Nawawi, Maimun; Effendy, Moh Hafid; Hamzah, Moh; Nurhidayatuloh, N. (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
This study examines Islamic Philanthropic practices (Zakat, Infaq, and Sadaqah) within a transnational context that has received limited scholarly attention, particularly among migrant workers. Legal issues arise from regulatory misalignment between Indonesia and Malaysia in Zakat governance, which affects the practice of religious obligations. The objective of this study is to introduce the concept of social delegitimation in relation to transnational religious obligations and to understand the process through which Madurese migrants in Malaysia fulfil Zakat, Infaq, and Sadaqah (ZIS). This research adopts an empirical study using anthropological and comparative approaches and applies Kenneth L. Pike's emic and etic perspectives. The findings indicate that the fulfilment of ZIS takes place through continuous negotiation within conditions of transnational uncertainty. Regulatory misalignment contributes to the social delegitimation of formal zakat institution in Malaysia, leading migrants to prefer channeling their ZIS through networks of kiai (religious scholars) and community groups in their hometowns, which are perceived to guarantee emotional proximity, blessing (barakah), and spiritual accountability. Accordingly, this study demonstrates that religious authority and the legitimacy of Islamic philanthropy in diaspora contexts are shaped more by social relations and transnational resilience strategies than by mere state legal frameworks.Penelitian ini mengkaji praktik filantropi Islam (zakat, infaq, dan sadaqah) dalam konteks transnasional yang jarang dieksplorasi, khususnya di kalangan pekerja migran. Terdapat isu hukum mengenai ketidakselarasan regulasi zakat antara Indonesia dan Malaysia yang memengaruhi praktik kewajiban agama. Tujuan studi ini adalah memperkenalkan konsep delegitimasi sosial terhadap kewajiban agama transnasional dan memahami proses pemenuhan zakat, infaq, dan sadaqah (ZIS) migran Madura di Malaysia. Metode yang digunakan adalah penelitian empiris dengan pendekatan antropologi dan komparatif, serta menerapkan perspektif emik dan etik Kenneth L. Pike. Hasil penelitian menunjukkan bahwa pemenuhan ZIS berlangsung melalui negosiasi berkelanjutan dalam situasi ketidakpastian transnasional. Ketidakselarasan regulasi mendorong delegitimasi sosial terhadap institusi zakat formal di Malaysia, menyebabkan migran lebih memilih menyalurkan ZIS melalui jaringan kiai dan komunitas di kampung halaman karena dinilai menjamin kedekatan emosional, keberkahan, dan akuntabilitas spiritual. Dengan demikian, kontribusi artikel ini memperlihatkan bahwa otoritas keagamaan dan legitimasi filantropi Islam di diaspora lebih ditentukan oleh relasi sosial dan strategi ketahanan transnasional daripada sekadar kerangka hukum negara.